Perlindungan Hukum Terhadap Kreditur Preferen Atas Objek Jaminan Yang Disita Kejaksaan Dalam Perkara Pidana Migas - Dewanto, Wisnu (Syntax Corporation, 2025)
In handling criminal cases, the authority of the court at all levels of examination over confiscated objects is in principle the same as the authority given by the law to the investigating agency and the public prosecutor. If the court's verdict states that the confiscated object is Confiscated for the State, then the confiscated object automatically becomes the property of the state and its execution is carried out based on the provisions stipulated in Article 273 paragraph (3) of KUHAP. Problems arise when assets seized by the prosecutor's office in a criminal case turn out to be an object of collateral in a credit that can harm preferred creditors. As has happened in a case at the Marabahan District Court, when there was a case verdict Number 46/Pid.Sus/2019/PN.Mrh related to oil and gas crimes, then the prosecutor's office, in this case the Barito Kuala District Attorney's Office, had the right to conduct an auction of evidence in the form of a fuel oil storage warehouse. However, later on, a lawsuit arose from PT Bukopin as a creditor and holder of a mortgage on the fuel oil storage warehouse which was then registered in Case Number 16/Pdt.Plw/2019/PN Mrh. Therefore, we need to know the extent of legal considerations (ratio decidendi) of the Marahan District Court Decision Number 16/Pdt.Plw/2019/PN Mrh and the legal protection of preferred creditors on collateral objects seized by the prosecutor's office in oil and gas criminal cases. This type of research is normative law using 3 (three) approaches that are studied through literature and document studies, then processed with decuctive logic. The results of this study indicate that the legal considerations (ratio decidendi) used by the Judge in case Number 16/Pdt.Plw/2019/PN Mrh are in line with the Supreme Court Decision Number 1731K/Pdt/2011 which confirms that the object of credit collateral that has been encumbered by mortgage rights that have been issued a Certificate of Mortgage, has inherent rights and interests and must receive legal protection. Thus, for future improvements, the legal protection of creditors holding Mortgage Rights as preferred creditors should be more guaranteed in the laws and regulations regarding Mortgage Rights in the event of confiscation of the object of Mortgage Rights by the prosecutor's office related to criminal acts, especially regarding oil and gas.